Language acquisition from the Khaldunian perspective - BELHMARI, Bachir; AOUISSI, Kamel (Social Sciences Journal, 2021)
Language is the basis of any society and the strength of its historical, cultural and civilizational entity. It is the most important Props of training for societies, and its role is not just to communication and communication between members of society, but rather is a reservoir of the ideas of society. To highlight its importance in society, perhaps the most prominent of these Muslim scholars is Abd al-Rahman Ibn Khaldun, who within this paper we will try to shed light on his most important efforts in the linguistic issue by defining the language from the Khalduni perspective, the method of its acquisition, and the method adopted by Ibn Khaldun in its development.